Multiple basilic vein aneurysms concomitant with multiple hemangiomas of the upper extremity: A case report - Yaylak, Faik (Pulsus Group Inc, 2007)
Basilic vein aneurysms are rare clinical entities. A 21-year-old woman with basilic vein aneurysms and multiple hemangiomas in the right upper extremity is presented. The case is discussed in light of the relevant literature with emphasis on the use of Doppler ultrasonography and magnetic resonance venography.